Cooperative intersection management for mixed traffic - Loh, Yi Xun (Nanyang Technological University, 2021)
The development of Automated and Connected Vehicles (CAVs) will change the way we travel in the future. CAV will bring about potential benefits such as safety and efficiency to our transportation system. With such immense potential for CAV, many research studies have studied the impact of CAV on our existing transportation system. While most of these researches only focused on a controlled CAV environment, with the gradual adoption rate of CAVs, CAVs will be sharing the roads with human-driven vehicles (HVs), posing a challenge to our current traffic management during this transition period. As there are significant differences between CAVs and HVs many changes have to be made to our existing traffic policies and infrastructures. In this Final Year Project, a hybrid intersection will be proposed for use in a mixed traffic environment. Simulation of the hybrid intersection will be set up in SUMO (Simulation of Urban MObility) under various CAV penetration rates, and its impact will be studied. The experiment results concluded that the implementation of the hybrid intersection increased the overall efficiency at higher CAV penetration rates and uncongested traffic flow rates.